Pengaruh Bimbingan Guru PAK Terhadap Disiplin Belajar Siswa Kelas V SD Negeri No.173525 Balige Tahun Pembelajaran 2024/2025 - Tripena Engelina Manullang; Tahadodo Waruwu; Risden Anakampun; Hasudungan Simatupang; Dame Taruli Simamora (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The purpose of this study was to determine the suspected positive and significant influence of PAK teacher guidance on the learning discipline of grade V students of SD Negeri No.173525 Balige in the 2024/2025 Academic Year. The method used in this study uses a quantitative research method with an inferential statistical descriptive approach. The population is all grade V students of SD Negeri No.173525 Balige in the 2024/2025 Academic Year, totaling 41 people and all of them are used as research respondents. Data were collected using a positive closed questionnaire of 45 items. The results of the data analysis showed that there was a positive and significant influence of PAK teacher guidance on the learning discipline of grade V students of SD Negeri No. 173525 Balige in the 2024/2025 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.628> rtable ( = 0.05, n = 41) = 0.308 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 5.044> ttable ( = 0.05, dk = n-2 = 39) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="4","03"+1.16X. b) Regression determination coefficient test (r2) = 39.5%. 3) Hypothesis testing using the F test obtained Fcount> Ftable=(=0.05, dknumerator k=16, dkdenominator=n-2=41-2=39) which is 25.43>1.51. Thus Ha, namely there is a positive and significant influence of PAK teacher guidance on the learning discipline of class V students of SD Negeri No.173525 Balige in the 2024/2025 Academic Year, is accepted and H0 is rejected.